Metabolic Pathway of Cyclosporine A and Its Correlation with Nephrotoxicity - Wu, Qinghua; Kuca, Kamil (Current Drug Metabolism, 2019)
Background: Cyclosporine A (CsA) is widely used for organ transplantation and autoimmune disorders. However, CsA nephrotoxicity is a serious side effect that limits the clinical use of CsA. The metabolism of CsA has a close relationship with this disease in renal-transplant patients. However, the metabolic pathways of CsA and its metabolizing enzymes have rarely been comprehensively reviewed. In this review, we have summarized the specific metabolic profiles of CsA in humans, especially renal-transplant patients. Moreover, the specific metabolizing enzymes and the potential roles that CsA metabolism plays in CsA nephrotoxicity were summarized and discussed. Methods: Electronic databases including PubMed, Web of Science, and Scifinder were searched with the keywords
Keywords: metabolizing enzymes